Isolated Word Recognition System for Hindi Language - Suman K, Saksamudre; Deshmukh, RR (International Journal of Computer Sciences and Engineering, 2025)
Speech is a natural mode of communication for people. So people are so comfortable with speech recognition systems. The overall performance of any speech recognition system is highly depends on the feature extraction technique and classifier. In this paper, we presented Isolated Word Recognition System for Hindi Language using MFCC as feature extraction and KNN as pattern classification technique. The system is trained for 10 different Hindi words. The experimental result of our system is that it gives 89% accuracy rate.